Optimasi Sucker Rod Pump (SRP Pada Sumur “TMT”-Y Lapangan X - Wahyu, Rafi; Risna, Risna; Firdaus, Firdaus; Ammiruddin, Ammiruddin; Afifah, Rohima Sera; Finansa , Dody (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The Sucker Rod Pump installed in the TMT-Y Field X experienced a decrease in production because the pump capacity that has been used for a longer tim e is no longer in accordance with the pump capacity. From the initial data the production rate was known to be 350 bpd, judging from the production capacity of the TMT-Y well in Field X, the value of Qmax was 415.55 bpd and the productivity index value of 1.1 into the classification of medium well performance, the well still has the potential to produce more. Therefore, performing pump optimization calculations to increase productivity, the previous method I used was optimization of five scenarios. This optimization is carried out using five scenarios, in scenario 1 using a 2- inch plunger with 5/8 and 7/8 inch rods to calculate the pump optimization in scenario 2 using a 2 inch plunger and 5/8 and 7/8 inch rods. The production rate in scenario 1 is 365.7 bpd, the pump stroke length is 94 inches and the pump speed is 7.4 spm. the results of scenario 2 obtained a production rate of 370.7 bpd, a pump stroke length of 91 inches and a pump speed of 6.6 spm. In the results of scenario 3, a production rate of 368.7 bpd a pump stroke length of 90 inches and a pump speed of 6.5 spm was obtained in scenario 4 the results obtained a production rate of 367.6bpd, 76-inch pump stroke length and 5.5spm pump speed. The result of scenario 5 cannot be used the results of the intersection and the flow rate. Among the five scenarios, the best scenario is scenario 2, because if you look closely, the production rate increases from the initial production flow rate, which is from 350 bpd, which is higher to 370.7 bpd.